Pengembangan Model Inkuiri (Inquiry Based Learning) Berbasis Picture And Picture Dalam Pembelajaran Teks Cerpen - Diana, Purwati Zisca; Hananditya, Arya; Wulandari, Putri Ayu; Fadilla, Annisa Rizky (Jumper: Journal of Educational Multidisciplinary Research, 2023)
This research and development aims to describe the Development of Picture and Picture-based Inquiry Models in learning short story texts in class XI SMA. The selection of this inquiry learning model is based on learning short story texts with this model which is carried out in schools that are not optimal and students are easily bored with learning short story texts that only use PPT media and other conventional media, while the picture and picture method itself is a learning method that explains material that through related images. This research is an R&D (Research and Development) study using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) method. The experimental subjects in this observation were carried out by material, learning, and teaching experts. Collecting data in this study used a questionnaire to validate teaching material products, observations at related schools, as well as interviews with teachers regarding existing problems and needs analysis. The data analysis technique uses the scoring method in assessing the validation results regarding teaching material products. The results of research on this product get the category "Very Eligible (SL)", this is evidenced by the elaboration of the values ​​obtained from the experts, including material experts get a score of 79 with a feasibility value of 98. Then from learning experts get a score of 76 with a feasibility value 89. Furthermore, the score obtained from the teaching experts gets a score of 68 with a feasibility value of 97. This indicates that this product can be applied to learning Indonesian, especially short story texts and can be directly tested.